An Analysis of Translational Shifts in the Original Soundtrack Translation of the Film ‘Rapunzel – Tangled (International Journal of Education and Literature, 2026)
This study explores the translation shifts found in the soundtrack of the film Rapunzel – Tangled, specifically in the German-to-Indonesian translation. The objective is to identify the types of translation shifts and analyze their distribution and tendencies during the translation process. The research data were taken from three songs: "Wann fängt mein Leben an?", "Mutter weiß mehr", and "Endlich sehe ich das Licht". A qualitative descriptive method was employed, focusing on lines containing translation shifts. Data were collected through documentation and analyzed based on Catford’s (1965) theory of translation shifts. A total of 74 translation shifts were identified, with the highest distribution in "Mutter weiß mehr" (32 shifts), followed by "Wann fängt mein Leben an?" and "Endlich sehe ich das Licht" (21 shifts each). In "Wann fängt mein Leben an?", structural shifts dominated, making up 38.9% of the shifts, followed by class and unit shifts (27.8% each), and intrasystem shifts at 5.5%. In "Mutter weiß mehr", structural shifts accounted for 35.4%, class shifts 34.1%, unit shifts 28%, and intrasystem shifts 2.4%. In "Endlich sehe ich das Licht", class shifts were the most prevalent (33.3%), followed by unit shifts (31.7%), structural shifts (30%), and intrasystem shifts (5%). The study concludes that structural and class shifts are the dominant strategies used in translating the soundtrack, helping to manage linguistic differences while maintaining meaning, musicality, and emotional impact in the target language.